Alternative Splicing May Not Be the Key to Proteome Complexity. Issue 2 (February 2017) - Tress, Michael L.; Abascal, Federico; Valencia, Alfonso
Abstract : Alternative splicing is commonly believed to be a major source of cellular protein diversity. However, although many thousands of alternatively spliced transcripts are routinely detected in RNA-seq studies, reliable large-scale mass spectrometry-based proteomics analyses identify only a small fraction of annotated alternative isoforms. The clearest finding from proteomics experiments is that most human genes have a single main protein isoform, while those alternative isoforms that are identified tend to be the most biologically plausible: those with the most cross-species conservation and those that do not compromise functional domains. Indeed, most alternative exons do not seem to be under selective pressure, suggesting that a large majority of predicted alternative transcripts may not even be translated into proteins. Trends: Although alternative splicing is well documented at the transcript level, large-scale proteomics experiments identify few alternative isoforms. Proteomics evidence also suggests that the vast majority of genes have a single dominant splice isoform. Alternative isoforms detected in proteomics experiments tend to be conserved, are highly enriched in subtle splice events such as mutually exclusively spliced homologous exons and events that do not disrupt functional domains. Recent large-scale RNA-seq studies have shown that tissue specificity seems to be controlled by gene expression rather than alternative splicing. Variant calling experiments show that most alternative exons are evolving neutrally, which suggests that most alternative splice events are not evolutionary innovations.